"Tom had us all doing front-end web development": a nostalgic (re)imagining of Myspace. Issue 1 (3rd April 2022) - Miltner, Kate M.; Gerrard, Ysabel
Abstract: This paper provides an analysis of a nostalgic Myspace discourse that contradicts the narrative of Myspace as a failed platform. The Myspace nostalgia discourse is especially dominant on Twitter and responds to what Miltner refers to as the "coding fetish discourse". It re-imagines Myspace through the lens of digital skill development and reinforces the framing of coding as a net good for social mobility, particularly for women and people of colour. It also offers trenchant critiques aimed at platform capitalism and platform governance that position Myspace as a foil for "toxic" and "gentrified" contemporary social media platforms. Contrary to previous popular framings of Myspace as an unsafe environment, Myspace coding Tweets offer a generative reimagining of Myspace as a place where young people learned valuable skills. In doing so, these Tweets take the very elements that supposedly caused Myspace's decline—its chaotic aesthetics and the dominance of people of colour and young women—and reposition them at the core of Myspace's value and worth. We argue that these nostalgic reframings of Myspace ultimately reflect contemporary discourses about coding and social media platforms: Myspace may have "died", but it is our current sociotechnical ideals and anxieties that brought it back to life.